Effects of elemental sulphur on heavy metal uptake by plants growing on municipal sewage sludge. (15th January 2016) - Dede, Gulgun; Ozdemir, Saim
Abstract: In this study experiment was carried out to determine the phytoextraction potential of six plant species ( Conium maculatum, Brassica oleraceae var. oleraceae, Brassica juncea, Datura stramonium, Pelargonium hortorum and Conyza canadensis ) grown in a sewage sludge medium amended with metal uptake promoters. The solubility of Cu, Cd and Pb was significantly increased with the application of elemental S due to decrease of pH. Faecal coliform number was markedly decreased by addition of elemental sulphur. The extraction of Cu, Cr and Pb from sewage sludge by using B. juncea plant was observed as 65%, 65% and 54% respectively that is statistically similar to EDTA as sulphur. The bioaccumulation factors were found higher (>1) in the plants tested for Cu and Pb like B. juncea . Translocation index (TI) calculated values for Cd and Pb were greater than one (>1) in both C. maculatum and B. oleraceae var. oleraceae . The results cleared that the amendment of sludge with elemental sulphur showed potential to solubilize heavy metals in phytoremediation as much as EDTA. Highlights: Heavy metal removal efficiency of sewage sludge by phytoextraction was investigated. Phytoextraction capacity was found higher in Brassica juncea plant. The availability of Cu, Cd and Pb were promoted by increasing dosage of sulphur. Abstract : Amendment of sludge with elemental sulphur holds potential for usage as an alternative to chemical amendments to solubilize heavy metals in phytoremediation.